Sensory neuronal sensitisation occurs through HMGB-1/RAGE and TRPV1 in high glucose conditions - Bestall, S.M.; Hulse, R.P.; Blackley, Z.; Swift, M.; Ved, N.; Paton, K.; Beazley-Long, N.; Bates, D.O.; Donaldson, L.F. (Company of Biologists, 2018)
Many potential causes for painful diabetic neuropathy have been proposed including actions of cytokines and growth factors. High mobility group protein B1 (HMGB1) is a RAGE agonist, increased in diabetes, that contributes to pain by modulating peripheral inflammatory responses. HMGB1 enhances nociceptive behaviour in naïve animals through an unknown mechanism. We tested the hypothesis that HMGB1 causes pain through direct neuronal activation of RAGE and alteration of nociceptive neuronal responsiveness. HMGB1 and RAGE expression were increased in skin and primary sensory (DRG) neurons of diabetic rats at times when pain behaviour was enhanced. Agonist-evoked TRPV1-mediated calcium responses increased in cultured DRG neurons from diabetic rats and in neurons from naïve rats exposed to high glucose concentrations. HMGB1-mediated increases in TRPV1-evoked calcium responses in DRG neurons were RAGE and PKC-dependent, and this was blocked by co-administration of the growth factor splice variant, VEGF-A165b. Pain behaviour and DRG RAGE expression increases were blocked by VEGF-A165b treatment of diabetic rats in vivo. HMGB-1-RAGE activation sensitizes DRG neurons in vitro. VEGF-A165b blocks HMGB-1/RAGE DRG activation, which may contribute to its analgesic properties in vivo.